2018
DOI: 10.1021/jacs.8b01042
|View full text |Cite
|
Sign up to set email alerts
|

Esterase-Catalyzed Siderophore Hydrolysis Activates an Enterobactin–Ciprofloxacin Conjugate and Confers Targeted Antibacterial Activity

Abstract: Enteric Gram-negative bacteria, including Escherichia coli, biosynthesize and deploy the triscatecholate siderophore enterobactin (Ent) in the vertebrate host to acquire iron, an essential nutrient. We report that Ent-Cipro, a synthetic siderophore-antibiotic conjugate based on the native Ent platform that harbors an alkyl linker at one of the catechols with a ciprofloxacin cargo attached, affords targeted antibacterial activity against E. coli strains that express the pathogen-associated iroA gene cluster. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
173
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(181 citation statements)
references
References 82 publications
7
173
0
1
Order By: Relevance
“…(a) Decomposition of the ciprofloxacin–enterobactin conjugate 3 . IroD‐catalyzed hydrolysis breaks apart the siderophore, leaving behind the monocatecholate product 4 (Neumann, Sassone‐Corsi, Raffatellu, & Nolan, ). (b) Ester prodrugs of the metalloproteinase proinhibitor PY‐2: methyl ester 7 , benzyl ether linked 8 , and catechol linked 9 .…”
Section: Esterase‐activated Prodrugsmentioning
confidence: 99%
“…(a) Decomposition of the ciprofloxacin–enterobactin conjugate 3 . IroD‐catalyzed hydrolysis breaks apart the siderophore, leaving behind the monocatecholate product 4 (Neumann, Sassone‐Corsi, Raffatellu, & Nolan, ). (b) Ester prodrugs of the metalloproteinase proinhibitor PY‐2: methyl ester 7 , benzyl ether linked 8 , and catechol linked 9 .…”
Section: Esterase‐activated Prodrugsmentioning
confidence: 99%
“…[31] Siderophores are small-molecule iron chelators produced, secreted, and taken up by bacteria to satisfy their supply of iron, which is an essential growth factor for them.G iven that bacterial resistance to established antibiotic is increasing worldwide, [32] the development of siderophore-drug conjugates has been identified as apromising Trojan horse strategy especially to address Gram-negative bacteria by linking antimicrobial drugs to siderophores, thereby facilitating the uptake anda ccumulation of antimicrobial drugs in the pathogens. [34][35][36] In their report, Miller and Ji link the Nterminus of ciprofloxacin 22 (Scheme 6) through an amide bond to the carboxylic acid of aT ML core and attach desferrioxamin B( 23), as iderophore and xenosiderophore of several Gram-positive and Gram-negative bacteria, through as hort succinyl spacer to the phenolic hydroxy group of aT ML moiety.R esulting desferrioxaminciprofloxacin conjugate 21 shows increased growth inhibitory activity against the Gram-negative pathogen Pseudomonasa er-uginosa in an agar diffusion assay compared to the parent ciprofloxacin and noncleavablea nalogue 24. [34][35][36] In their report, Miller and Ji link the Nterminus of ciprofloxacin 22 (Scheme 6) through an amide bond to the carboxylic acid of aT ML core and attach desferrioxamin B( 23), as iderophore and xenosiderophore of several Gram-positive and Gram-negative bacteria, through as hort succinyl spacer to the phenolic hydroxy group of aT ML moiety.R esulting desferrioxaminciprofloxacin conjugate 21 shows increased growth inhibitory activity against the Gram-negative pathogen Pseudomonasa er-uginosa in an agar diffusion assay compared to the parent ciprofloxacin and noncleavablea nalogue 24.…”
Section: Different Triggers For Trimethyl Lockmentioning
confidence: 99%
“…[49][50][51] Scheme7.Esterase-sensitiveT ML prodrugs of hydrogen sulfide. [50] Furthermore, desymmetrization of rhodamine-110 (35)t hrough the attachment of only one TML acetate gives the opportunity to functionalize the second amino group for the development of fluorogenic chemicalp robes (Scheme 9). PLE = porcinel iver esterase, PBS = phosphate-buffered saline.…”
Section: Different Triggers For Trimethyl Lockmentioning
confidence: 99%
See 1 more Smart Citation
“…[2c] Thus,t here is an urgent need for developing new antimicrobial approaches against MDR bacterial pathogens.Besides investigating novel agents against new targets in bacteria [3] via previously unexplored mechanisms,a nother strategy is to enhance the efficacya nd safety of the existing antibiotics via drug combinations or increasing the specificity.F or example, Kahne et al demonstrated that the use of novobiocin analogues greatly lowers the dose of polymyxins required to treat Gram-negative bacteria by inhibiting DNAg yrase,b inding LptB,a nd disrupting the outer membrane. [4] Yanetalreported nanoaggregates of ciprofloxacin for inhibiting E. coli. [4] Yanetalreported nanoaggregates of ciprofloxacin for inhibiting E. coli.…”
mentioning
confidence: 99%